Current clinical landscape of oncolytic viruses as novel cancer immunotherapeutic and recent preclinical advancements - Yun, Chae-Ok; Hong, JinWoo; Yoon, A-Rum (Frontiers in Immunology, 2022)
Oncolytic viruses (OVs) have been gaining attention in the pharmaceutical industry as a novel immunotherapeutic and therapeutic adjuvant due to their ability to induce and boost antitumor immunity through multiple mechanisms. First, intrinsic mechanisms of OVs that enable exploitation of the host immune system (e.g., evading immune detection) can nullify the immune escape mechanism of tumors. Second, many types of OVs have been shown to cause direct lysis of tumor cells, resulting in an induction of tumor-specific T cell response mediated by release of tumor-associated antigens and danger signal molecules. Third, armed OV-expressing immune stimulatory therapeutic genes could be highly expressed in tumor tissues to further improve antitumor immunity. Last, these OVs can inflame cold tumors and their microenvironment to be more immunologically favorable for other immunotherapeutics. Due to these unique characteristics, OVs have been tested as an adjuvant of choice in a variety of therapeutics. In light of these promising attributes of OVs in the immune-oncology field, the present review will examine OVs in clinical development and discuss various strategies that are being explored in preclinical stages for the next generation of OVs that are optimized for immunotherapy applications.